Hyperboreans : Myth and history in Celtic-Hellenic contacts - Bridgman, Timothy P. (Trinity College (Dublin, Ireland). Department of Classics, 2001)
In the course of Greek literary history, six authors wrote texts which identify the Hyperboreans, a totally m ythical people who worshipped Apollo, with Celts, a real northern neighbour of the Greeks, or the Hyperboreans lands with Celtic ones. The immediate purpose of the present work has been to examine which texts make this identification, in what contexts they were identified one with another, and, lastly, why these authors identified a mythical people with a real one. It has been the present author's contention throughout this thesis that these texts were not just written by chance by authors who were cranks or who liked to invent tall tales, but that the answers to the questions put forward above were to be sought within the context of the foundations of Greek culture, thought and literature, in the backgrounds of the authors them selves, in the current philosophical trends of their times and in the history of Celtic- Hellenic contacts in the western Mediterranean.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin